Dataset for multimodal transport analytics of smartphone users - Collecty - Martina Erdelić; Tomislav Erdelić; Tonči Carić (Data in Brief, 2023)
Urban mobility is facing many challenges, such as energy consumption, pollution, and safety. Therefore, it is necessary to analyze the mobility of users through the transportation network using data containing information regarding the used transport mode. This data article describes a dataset from mobile devices collected by users as they move through the transportation network. Each sample in this dataset is labelled with a corresponding transport mode. Eight transport modes are present in the dataset: Car, Bus, Walking, Bicycle, Train, Tram, Running and Electric Scooter. The basic breakdown of the raw data according to users, transport modes and multimodal routes is presented. During data collection, data from the accelerometer, magnetometer, and gyroscope sensors mounted within the mobile device were stored. The data were collected using a mobile application from mobile devices with an embedded Android operating system. The structure of the text files in which the data were stored and the structure of the application used to collect the data are presented in the paper. The collected data provides a highly relevant basis for mobility analysis and planning, analysis of road conditions, clustering of user behaviour, and comparison of transport mode classification methods.